Depression of administrative-territorial units of Chernivtsi oblast: social-geographical assessment - Костащук, Іван Іванович; Білоус, Юрій Олександрович; Ячнюк, Марина Олександрівна (My University, 2021)
Problem Statement and Purpose. The world economy has always developed and continues to develop cyclically, which affects the economic development of individual countries and their regions. As a result of cyclical economic development, regions are formed that maintain a progressive or stagnant type of economic development, and some of them, especially during periods of economic crisis, develop a regressive type. Thus, depressed regions or their separate territories appear, the study of which aims to identify in time the territorial disparities and polarizations of different types of the social formation of administrative units and to establish the level of their depression. It should be noted that most of the available scientific achievements concern the study of the territory of Ukraine at the regional level, and not at the subregional (raion) level. Therefore, our research allows us to shed more light on the depression of administrative-territorial units of Chernivtsi oblast, which differs from other regions of Ukraine by its natural-geographical, demographic, ethnic contrast, as well as cross-border and border position, which certainly has a significant impact on depression of regions and cities of regional significance. The purpose of this study is to conduct a socio-geographical assessment of the depression of administrative-territorial units of Chernivtsi oblast, which allows us to learn about the current state of the oblast and its raions in terms of depression, as well as identify possible steps to solve this problem. Data & Methods. To study the depression of administrative-territorial units of Chernivtsi oblast, the following main types were chosen: economic, social, and demographic. For each of these blocks, the main indicators of indicators were determined, according to which a socio-geographical assessment of the level of depression in administrative regions and cities of regional significance was conducted. Having established the rating places for each administrative-territorial unit according to the selected indicators, or their relative values, it was possible to establish the average place of each unit and, accordingly, the level of depression for each of the studied blocks. It was also established the common place of administrative units in the region by all indicators and thus identified different, according to the level of depression, regions. Results. With the help of rating research, the typification of administrative-territorial units of the oblast according to the level of economic, social, demographic, and integral depression was carried out. The most depressed were the agricultural raions of the oblast – Khotyn, and Sokyriany. However, it should be noted that Khotyn raion has the same types of depression in all its components, and in Sokyriany raion the worst is the demographic situation, and the best ‒ the economic one. The lowest level of depression is characteristic of Storozhynets raion, which is explained by its favorable geographical location relative to the oblast center, which contributes to economic and social development, as well as polyethnicity, which strengthens the demographic component.
Keywords: territory depression; economic depression; demographic depression; social depression; level of education; level of welfare